Numerical literacy profile of biology students in plant physiology practicum and level of conceptual change - Diana, Sariwulan (Universitas Negeri Jakarta, 2025)
Plant physiology is material that is considered difficult, and studying it requires adequate numeracy literacy, especially in practicums. Thus, it is necessary to reveal the student's numeracy literacy profile and the level of conceptual change before and after the practicum. This study used a pre-experimental design with a pre-test and post-test group. The pre-test regarding numeracy literacy, which refers to the Minimum Competency Assessment, is given to Biology Education Department students who are contracting the Plant Physiology course in the odd semester 2022/2023, conducted before practicum about accumulation of mineral nutrients in plant cells, nutrient culture, water potential, and osmotic potential. After each practicum, students are assigned to answer response questions, and it ends with a post-test. The results showed that there was an increase in student numerical literacy from the very low category (42.7) into the moderate category (62.1) with level of conceptual change in the construction and N-gain in low categories. Although it has the potential to improve students' numeracy literacy, the Plant Physiology practicum needs to be improved, for example, by involving practical students in preparing substances and strengthening the lecturers in their responses.